Reproductive wastage analysis of Daldale ewes using a twice yearly lambing program - Putu, I. Gede (Indonesian Animal Sciences Society, 1995)
Reproductive wastage analysis of intensification sheep farming system using a twice yearly lambing program was carried out using Daldale ewes . Study was focused on ewes which completed a three-year study and alloted into 96 ewes involved in a twice-yearly lambing program (TY) and 105 ewes involved in once-yearly lambing program (OY) . Results indicated that 44 ewes (45 .8%) and 32 ewes (33 .3%) out of 96 ewes in TY group mated four and five times, respectively during five consecutive mating opportunities . However, those mating frequencies were not associated with increasing number of lambs bom per ewe raddled . It was due mainly to high percentage of ewes failed to mate after parturition, fertilization failure and embryonic mortality which were indicated by low percentage of mated ewes giving birth . It can be concluded that twice-yearly lambing program still needs further study particlularly in using different breed . Another alternative which needs to be studied is the use of a three lambing program in two years period at which the ewes have more chances to prepare their physical and physiological conditions before the next pregnancy . Key words : Reproductive wastage, sheep, lambing program